PENGELOLAAN KEUANGAN PEMUDA BUDDHIS BUDDHA SASANA XIAN MA BERDASARKAN SILA, ETIKA, DAN TATA KELOLA - Yordi Inggarsono; Yakobus K Bangun; Marselinus Asri (AJAR, 2021)
This study aims to explore the principles of eight precepts and ethical perspectives on the Pemuda Buddhis Buddha Sasana Xian Ma in financial management. The research method uses an interpretive paradigm with a phenomenological approach. The results showed that the eight precepts and eight noble paths of the Buddha's teachings have the meaning of an ethical perspective and if they are carried out simultaneously, they will get thirty-eight major blessings in the form of ethics that must be implemented every day so that they affect the organizational ethics of the Pemuda Buddhis Buddha Sasana Xian Ma, which is responsible and prioritize virtue. This research is expected to contribute in the form of theory development and concept reconstruction, as well as additional literature on the eight precepts, eight noble paths and thirty-eight major blessings. This research can also provide an understanding and material for evaluating policies in realizing good ethics at Vihara.